2017
DOI: 10.1001/jamacardio.2017.0175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monthly High-Dose Vitamin D Supplementation on Cardiovascular Disease in the Vitamin D Assessment Study

Abstract: IMPORTANCE Cohort studies have reported increased incidence of cardiovascular disease (CVD) among individuals with low vitamin D status. To date, randomized clinical trials of vitamin D supplementation have not found an effect, possibly because of using too low a dose of vitamin D. OBJECTIVE To examine whether monthly high-dose vitamin D supplementation prevents CVD in the general population. DESIGN, SETTING, AND PARTICIPANTSThe Vitamin D Assessment Study is a randomized, double-blind, placebo-controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
333
2
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(357 citation statements)
references
References 38 publications
11
333
2
11
Order By: Relevance
“…Studies have not demonstrated improved cardiovascular outcomes in the general population with a therapeutic supplementation of deficient vitamins, such as vitamin D. 46 Even sparser is the evidence of cardiovascular benefit in the general population without a confirmed vitamin deficiency, other than possible theoretical benefits suggested in in vitro studies. 47,48 Furthermore, several studies demonstrated that routine vitamin and mineral supplementation in certain populations, for instance in elderly patients, could lead to a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have not demonstrated improved cardiovascular outcomes in the general population with a therapeutic supplementation of deficient vitamins, such as vitamin D. 46 Even sparser is the evidence of cardiovascular benefit in the general population without a confirmed vitamin deficiency, other than possible theoretical benefits suggested in in vitro studies. 47,48 Furthermore, several studies demonstrated that routine vitamin and mineral supplementation in certain populations, for instance in elderly patients, could lead to a worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent meta-analysis on non-skeletal effects of vitamin D supplementation demonstrates that most trials have been done in subjects without low 25[OH]D levels limiting the credibility of the argument that vitamin D supplementation has no potential benefit on outcomes in people with 25[OH] D insufficiency [1]. The Vitamin D Assessment study (ViDA) in 5100 healthy subjects, aged > 50 years, recently reported that 100,000 IU oral vitamin D 3 monthly was neutral for the prevention of CV disease [49,50], with a low rate of 25[OH]D deficiency in participants (25%), a lower than expected endpoint rate and monthly doses cited as possible reasons [51]. Metaanalysis and data from ViDA and other studies describe that benefits on clinical outcomes are greatest in the most deficient, and in studies using daily dosing regimens (as in VINDICATE) rather than monthly [52][53][54][55].…”
Section: Vitamin D As An Interventionmentioning
confidence: 99%
“…Moreover, Brøndum-Jacobsen et al (11) found that genetically reduced plasma 25-hydroxyvitamin D (25(OH)D) is not associated with increased risk of ischemic heart disease. Moreover, the results of Scragg et al's (12) randomized controlled trial (RCT) study showed no evidence that monthly high-dose vitamin D supplementation (100,000 IU a month) prevented cardiovascular diseases.…”
mentioning
confidence: 99%